Indicators for monitoring sustainable development goals: an application to oceanic development in the European Union - Rickels, Wilfried; Dovern, Jonas (Earth's future, 2016)
The 2030 Agenda for Sustainable Development includes a set of 17 sustainable development goals (SDG) with 169 specific targets. As such, it could be a step forward in achieving efficient governance and policies for global sustainable development. However, the current indicator framework with its broad set of individual indicators prevents straightforward assessment of synergies and trade-offs between the various indicators, targets, and goals, thus, heightening the significance of policy guidance in achieving sustainable development. With our detailed analysis of SDG 14 (Ocean) for European Union (EU) coastal states, we demonstrate how the (complementary) inclusion of composite indicators that aggregate the individual indicators by applying a generalized mean can provide important additional information and facilitate the assessment of sustainable development in general and in the SDG context in particular. Embedded in the context of social choice theory, the generalized mean varies the specification of substitution elasticity and thus allows: (a) for a straightforward distinction between a concept of weak and strong sustainability and (b) for straightforward sensitivity analysis. We show that while in general the EU coastal states have a fairly balanced record at the SDG 14 level, certain countries like Slovenia and Portugal with a fairly balanced and a fairly unbalanced showing, respectively, rank very differently in terms of the two concepts of strong sustainability.